2021
DOI: 10.5569/2340-5104.09.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Inclusión laboral y discapacidad invisible. Hacia una reflexión sobre las barreras y posibilidades del mercado laboral ordinario

Abstract: Este trabajo tiene como objetivo analizar la situación laboral de las personas con fibrosis quística en España, con qué barreras se encuentran en el acceso y mantenimiento del empleo y qué adaptaciones favorecerían la inserción. Los datos se obtuvieron de una muestra de 368 personas con fibrosis quística residentes en España de entre 16 y 60 años. Se utilizó una metodología mixta combinando encuestas, entrevistas y un grupo de discusión. Los hallazgos sugieren que la rigidez del mercado de trabajo ordinario no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…They have showed that living with cystic fibrosis is not necessarily associated with negative effects on career development (Saldana et al, 2018), and that people with cystic fibrosis face barriers to employment similar to "those experienced by other disabled people" (Edwards and Boxall, 2010). The inflexibility of employers toward needs for adaptations can represent a major barrier to employment for people with cystic fibrosis, as shown by a study in Spain (Esteban Romani et al, 2021).…”
Section: Living Longer With Cystic Fibrosis: Managing Illness and Acc...mentioning
confidence: 99%
“…They have showed that living with cystic fibrosis is not necessarily associated with negative effects on career development (Saldana et al, 2018), and that people with cystic fibrosis face barriers to employment similar to "those experienced by other disabled people" (Edwards and Boxall, 2010). The inflexibility of employers toward needs for adaptations can represent a major barrier to employment for people with cystic fibrosis, as shown by a study in Spain (Esteban Romani et al, 2021).…”
Section: Living Longer With Cystic Fibrosis: Managing Illness and Acc...mentioning
confidence: 99%